A powerful diagnostic tool for 21st Century management. Issue 1 (22nd February 2021) - Denning, Stephen
Abstract : Purpose: The author offers The Principles, Processes, Practices (PPP) Worksheet, an analytic tool that can help firms diagnose their current status in relation to the transformation from 20th Century to 21st Century management. Design/methodology/approach: The author posits that there are currently two strikingly different ways of running a corporation in a coherent and consistent fashion. The predominant mode of 20th Century management refined over the last 50 years has the goal of maximizing shareholder value. 10;By contrast, for 21st Century management–the pioneering mode of Agile enterprises and of leading Silicon Valley firms, the goal leads to principles and processes that enable agility. The principles and processes help firms mobilize talent to create instant, intimate, incremental value for customers. 10; Findings: The Principles, Processes, Practices (PPP) Worksheet an be applied either to the entire organization or to any part of that organization, such as the leadership team, or any department, or any team, at any point in time. Practical implications: Leaders using the PPP worksheet will become, in effect, what Richard Sheridan, CEO of Menlo Innovations, calls "a high tech anthropologist" probing what is going on. Originality/value: This is the first description of a potent analytical tool that can help a firm plan and implement a management transformation to 21st Century Agile practices.